Embryonal and Alveolar Rhabdomyosarcoma in Adults: Real-Life Data From a Tertiary Sarcoma Centre. Issue 1 (January 2020) - Drabbe, C.; Benson, C.; Younger, E.; Zaidi, S.; Jones, R.L.; Judson, I.; Chisholm, J.; Mandeville, H.; Fisher, C.; Thway, K.; Al Muderis, O.; Messiou, C.; et al.
Abstract: Aims: Embryonal and alveolar rhabdomyosarcoma (ERMS, ARMS) are subtypes of RMS that mainly occur in children, with relatively good outcomes. The incidence in adults is extremely low and survival is significantly worse compared with children. Data are scarce and literature generally combines all RMS subtypes, including pleomorphic RMS, which primarily occurs in adults and behaves more like undifferentiated pleomorphic sarcoma. The aim of this study was to evaluate patient and tumour characteristics, outcome and prognostic factors in adult patients with ERMS and ARMS. Materials and methods: All adult (18 years or older) ERMS and ARMS patients (presenting 1990–2016) were identified from a prospectively maintained database and were included in this analysis. Results: Overall, 66 patients were included (42 men, 24 women). The median age at presentation was 28 years (range 18–71). The median overall survival for all ARMS ( n  = 42) and ERMS ( n  = 24) patients was 18 months, with a 5-year overall survival rate of 27%. Patients presenting with localised disease ( n  = 38, 58%) and metastatic disease ( n  = 25, 42%), had a 5-year overall survival rate of 36% and 11%, respectively. In univariate analysis we found alveolar subtype, fusion gene positivity, infiltrative tumour and metastatic presentation to be negative prognostic factors. Conclusion: Survival in adult ERMS and ARMS patients is poor and the current data may be useful in the design of trials with novel agents. Ideally, paediatric and adult oncologists should set up trials together to get a better understanding of biological, genetic and clinically relevant factors in this disease. Highlights: Embryonal RMS (ERMS) and alveolar RMS (ARMS) are extremely rare in adults. 66 adult patients with ERMS and ARMS treated in a referral centre were studied. 42% of patients had metastatic disease at diagnosis. The 5-year overall survival of all patients was 27% and for metastatic patients was 11%. Survival in adult patients is much poorer than in paediatric patients.